2007
DOI: 10.1063/1.2436886
|View full text |Cite
|
Sign up to set email alerts
|

Methodological aspects in the calculation of parity-violating effects in nuclear magnetic resonance parameters

Abstract: We examine the quantum chemical calculation of parity-violating (PV) electroweak contributions to the spectral parameters of nuclear magnetic resonance (NMR) from a methodological point of view. Nuclear magnetic shielding and indirect spin-spin coupling constants are considered and evaluated for three chiral molecules, H2O2, H2S2, and H2Se2. The effects of the choice of a one-particle basis set and the treatment of electron correlation, as well as the effects of special relativity, are studied. All of them are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 42 publications
2
23
0
Order By: Relevance
“…Other proposed experiments include measurement of frequency splittings in nuclear magnetic resonance (NMR), EPR, microwave (MW) and Mössbauer spectroscopy. Alternative approaches aim for instance at a measurement of time‐dependence in optical activity or at the direct detection of the absolute value of the parity violating energy difference in the electronic ground state or electronically excited states .…”
Section: …For Chiral Molecules?mentioning
confidence: 99%
See 1 more Smart Citation
“…Other proposed experiments include measurement of frequency splittings in nuclear magnetic resonance (NMR), EPR, microwave (MW) and Mössbauer spectroscopy. Alternative approaches aim for instance at a measurement of time‐dependence in optical activity or at the direct detection of the absolute value of the parity violating energy difference in the electronic ground state or electronically excited states .…”
Section: …For Chiral Molecules?mentioning
confidence: 99%
“…A different numerical route is required to predict parity violating effects in NMR spectra of chiral compounds . For this purpose, linear and nonlinear response theoretical approaches are employed to compute parity violating contributions to NMR shielding tensors and indirect spin–spin coupling constants.…”
Section: …For Chiral Molecules?mentioning
confidence: 99%
“…I varies significantly near the equilibrium geometry as a function of the dihedral angle. 20,22,64,65 This compound has a torsional mode around the OO bond, giving rise to a double minimum potential. The property of interest may depend on nuclear geometry, and it needs to be averaged over the vibrational ground state, giving rise to the zero-point vibrational averages (ZPVA) correction.…”
Section: Chf-(i) Chf-(v)mentioning
confidence: 99%
“…Laubender and Berger found that PV in NMR shielding constants for the heavy elements in H 2 O 2 , H 2 S 2 , and H 2 Se 2 computed at the CCSD level of theory deviate from their uncorrelated counterparts typically by approximately 20%, with varying more pronounced corrections at the equilibrium structures, while in 2-fluorooxirane, electron correlation changes the shielding constants by almost 100% [168]. For the same H 2 X 2 molecules at their equilibrium structures, Weijo et al found that coupled-cluster and DFT results for PV contributions differ significantly from the HF data, that is, for the 77 Se PV shift in the nuclear shielding constant for H 2 Se 2 , they obtain (in 10 À10 ppm) 256.1 (HF), 139.9 (CCSD), 116.8 (B3LYP), 60.5 (BP86), 128.6 (PBE0), and 68.6 (PBE) [173]. Similarly, for the PV contribution to the Se-Se spin-spin coupling, they calculate (in nHz) À6.606 (HF), À3.181 (CCSD), À3.038 (B3LYP), À1.943 (BP86), À3.795 (PBE0), and À2.081 (PBE).…”
Section: Theoretical Predictionsmentioning
confidence: 99%
“…Similarly, for the PV contribution to the Se-Se spin-spin coupling, they calculate (in nHz) À6.606 (HF), À3.181 (CCSD), À3.038 (B3LYP), À1.943 (BP86), À3.795 (PBE0), and À2.081 (PBE). They also showed that basis set effects are very pronounced, especially at the correlated level of theory, and that the choice of the nuclear charge distribution model (point charge or extended Gaussian) has a significant impact on the PV contribution in the spin-spin coupling constant [173]. Vibrational effects in parity-violating contributions to the isotropic nuclear magnetic resonance chemical shift were recently investigated for CHFClBr by Weijo et al [174].…”
Section: Theoretical Predictionsmentioning
confidence: 99%